The spectral features and detectability of small, cyclic silicon carbide clusters - Christopher M. Sehring; C. Zachary Palmer; Brent R. Westbrook; Ryan C. Fortenberry (Frontiers in Astronomy and Space Sciences, 2022)
Rovibrational spectral data for several tetra-atomic silicon carbide clusters (TASCCs) are computed in this work using a CCSD(T)-F12b/cc-pCVTZ-F12 quartic force field. Accurate theoretical spectroscopic data may facilitate the observation of TASCCs in the interstellar medium which may lead to a more complete understanding of how the smallest silicon carbide (SiC) solids are formed. Such processes are essential for understanding SiC dust grain formation. Due to SiC dust prevalence in the interstellar medium, this may also shed light on subsequent planetary formation. Rhomboidal Si2C2 is shown here to have a notably intense (247 km mol−1) anharmonic vibrational frequency at 988.1 cm−1 (10.1 μm) for ν2, falling into one of the spectral emission features typically associated with unknown infrared bands of various astronomical regions. Notable intensities are also present for several of the computed anharmonic vibrational frequencies including the cyclic forms of C4, SiC3, Si3C, and Si4. These features in the 6–10 μm range are natural targets for infrared observation with the James Webb Space Telescope (JWST)’s MIRI instrument. Additionally, t-Si2C2, d-Si3C, and r-SiC3 each possess dipole moments of greater than 2.0 D making them interesting targets for radioastronomical searches especially since d-SiC3 is already known in astrophysical media.